Pituitary stalk craniopharyngioma - Figueiredo, Eberval Gadelha (BMJ Publishing Group, 2011)
Craniopharyngiomas are benign but aggressive neoplasms arising along the craniopharyngeal duct. It is frequently located in the suprasellar region. Primarily pituitary stalk craniopharyngioma is unusual and uncommonly early diagnosed, before it enlarges and extends to supra or parasselar region. This unusual location and the small size pose therapeutic dilemmas, since it has the ability to grow larger. Currently, no consensus exists regarding the optimal management. The authors have recommended complete resection.